Effective School For Early Childhood (Educational Management Perspective) - Maimunah Maimunah; Aslamiah Aslamiah; Noorhapizah Noorhapizah; Novitawati Novitawati (ARZUSIN, 2025)
Efforts to achieve quality and effective early childhood education continue to demand focused attention, particularly in regions with limited resources. This qualitative study examines effective early childhood education institutions from an educational management perspective, utilizing a descriptive case study design involving three schools in South Kalimantan, Indonesia. Data were collected through participant observation, in-depth interviews, and document analysis, and analyzed using Miles and Huberman's interactive model with triangulation to ensure credibility. The study explores three central aspects: the role of principals’ leadership in cultivating effective school culture, strategies for managing learning environments, and the implementation of quality assurance systems. Findings indicate that effective early childhood education institutions are distinguished by transformational leadership practices adapted to local contexts, incorporating idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Holistic learning environment management includes the use of learning centers, positive discipline, strategic physical space organization, efficient time management, creative resource utilization, and the promotion of a supportive socio-emotional climate. Additionally, robust quality assurance is achieved through the application of Plan-Do-Check-Act (PDCA) cycles, authentic assessment, detailed documentation, and collaborative stakeholder engagement. The study concludes that the effectiveness of early childhood education institutions is driven not by material wealth or location but by the synergy of adaptive leadership, child-centered learning environment management, and participatory quality assurance mechanisms. These findings offer practical insights for policymakers and educators seeking to strengthen early childhood education in diverse and resource-limited contexts.